2011
DOI: 10.1590/s0100-29452011005000006
|View full text |Cite
|
Sign up to set email alerts
|

Modified atmosphere packaging extending the storage life of 'douradão' peach

Abstract: -'Douradão' peach is a perishable product and when cold stored is subject to chilling injury. The objective of the experiment was to evaluate the effect of modified atmosphere packaging (MAP) and cold storage on quality and storage life of these peaches. Fruits were packed in polypropylene (PP) trays and placed inside low density polyethylene (LDPE) bags (30, 50, 60, 75 µm thickness) with active modified atmosphere (10 kPa CO 2 + 1.5kPa O 2 , balance N 2 ). The control was made with peaches held in nonwrapped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…As a typical climacteric fruit, the preservation period of the ‘Yonglian No.1’ peach is short at room temperature. In peaches and nectarines, MAP slows down the respiration rate of fruits and retards the decrease in titratable acidity values, maintaining the fruit sugar and soluble solids content, flesh firmness, vitamin C and juice content, and slows deterioration through decreasing fruit injury and browning development [ 15 ]. This study demonstrated that MAP is an excellent addition to 4 ± 1 °C temperature management for extending the storage life of ‘Yonglian No.1’ peaches produced in Fujian province.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a typical climacteric fruit, the preservation period of the ‘Yonglian No.1’ peach is short at room temperature. In peaches and nectarines, MAP slows down the respiration rate of fruits and retards the decrease in titratable acidity values, maintaining the fruit sugar and soluble solids content, flesh firmness, vitamin C and juice content, and slows deterioration through decreasing fruit injury and browning development [ 15 ]. This study demonstrated that MAP is an excellent addition to 4 ± 1 °C temperature management for extending the storage life of ‘Yonglian No.1’ peaches produced in Fujian province.…”
Section: Discussionmentioning
confidence: 99%
“…This has the effect of delaying ripening, suppresses the decay of fresh fruit, inhibits the degradation of chlorophyll and other pigments, and maintains the organoleptic properties and fresh-like characteristics of the fruit [ 12 , 13 , 14 ]. This could also have an influence on reducing the loss of weight and could prevent the postharvest decay of ‘Douradão’ peaches [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Choi and Lee (1997) observed a significant effect on the reduction of woolliness using a passive modified atmosphere in 'Yumyeong' peaches when the fruits were compared with unpackaged ones. Santana, Benedetti, Sigrist, and Sarantopóulos (2010) and Santana, Benedetti, Sigrist, and Sato (2011) observed a significant reduction in woolliness with the use of active modified atmosphere and LDPE packaging (with values of 1% O 2 and 3% CO 2 ).…”
Section: Woolliness Index Internal Browning Index Pme and Pg Activitymentioning
confidence: 97%
“…However, changes in the levels of O 2 and CO 2 should not exceed the critical limit to prevent the occurrence of physiological disorders such as fermentation (Beaudry, 1999). Studies indicate that the use of passive modified atmosphere in peaches under cold storage reduces the loss of weight and firmness and may decrease chilling injuries in some cultivars (Santos, Castro, Picoli, & Rolim, 2008;Santana, Benedetti, Sigrist, & Sarantopóulos, 2010). After evaluating the use of polypropylene and polyethylene, Akbudak and Eris (2004) reported that these packages were efficient in maintaining the quality of 'Flavorcrest' peaches and 'Fantasia' nectarines for 30 and 45 days of storage, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Esta técnica consiste na redução do O 2 e aumento do CO 2 , reduzindo assim a síntese de etileno e, com isso, prolongando a vida pós-colheita dos frutos (Mendonça et al, 2015). Outros efeitos do uso dessa técnica em produtos frescos, durante a comercialização, podem incluir a redução da taxa respiratória, a minimização da perda de massa e a manutenção da cor e da firmeza, o que, consequentemente, pode contribuir para o retardo do amadurecimento (Santana et al, 2010).…”
Section: Introductionunclassified